2012
DOI: 10.1093/icvts/ivs320
|View full text |Cite
|
Sign up to set email alerts
|

In patients with corrosive oesophageal stricture for surgery, is oesophagectomy rather than bypass necessary to reduce the risk of oesophageal malignancy?

Abstract: A best evidence topic in cardiothoracic surgery was written according to a structured protocol. The question addressed was, 'is there an increased risk of cancer in a non-resected corrosive oesophageal stricture?' Altogether, 133 papers were found using the reported search; six papers were identified that provided the best evidence to answer the question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these studies were tabulated. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 4 publications
0
19
0
4
Order By: Relevance
“…Optimal management of esophageal corrosive injuries remains a debatable issue. There has been a controversy about whether the long-term benefits of esophagectomy outweigh the possible complications [2] , [4] . Moreover, it has yet to be precisely determined whether a partial esophagectomy is sufficient enough to reduce the risk of cancer or a more radical surgical management should be followed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal management of esophageal corrosive injuries remains a debatable issue. There has been a controversy about whether the long-term benefits of esophagectomy outweigh the possible complications [2] , [4] . Moreover, it has yet to be precisely determined whether a partial esophagectomy is sufficient enough to reduce the risk of cancer or a more radical surgical management should be followed.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological impact on the gastrointestinal tract and systematically varies significantly, depending on the acidic or the alkaline load along with the level of ionization and the duration of exposure [1] . As far as the management is concerned, it should be initially conservative while surgical approaches are implemented in case of complications such as perforation or stenosis [1] ; however, this issue remains controversial taken into consideration the fact that caustic ingestion significantly increases the long-term risk of esophageal squamous carcinoma development [1] , [2] . Herein, we report a case of a patient that developed squamous esophageal cancer on the ground of a caustic injury caused by ingestion of acidic substance, for which she had undergone near total esophagogastrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Hopkins et al [10] reported that the prevalence of prior corrosive injury in the patients presenting with esophageal carcinoma ranged from 1.0 to 4.0 %. In another study, Okonta et al [11] reviewed 198 patients who had corrosive esophageal stricture resulting from corrosive injury, and 50 of them (25.3 %) developed esophageal cancer. The lack of large multicenter studies makes it difficult to estimate the exact risk of esophageal carcinoma after caustic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the doubled mortality rate (11.0% vs 5.9%) of resection vs by-pass and the associated inadvertent damage to the trachea and laryngeal nerves support a conservative strategy especially in adult patients. The surgical treatment for gastric outlet obstruction is simple pyloroplasty for moderate strictures and gastrojejunostomy or partial gastrectomy for more extensive stricture [69][70][71].…”
Section: Late Complication and Treatmentmentioning
confidence: 99%